IMPLEMENTATION OF GUIDANCE FOR FOREIGN PRISONERS (PAPUA NEW GUINEA) AT THE CLASS II A NARCOTICS PRISON IN JAYAPURA - Helena Morin; Syahrial Yuska (Universitas Nusa Cendana, 2026)
This study examines the implementation of rehabilitation programs for foreign inmates from Papua New Guinea (PNG) at the Class IIA Narcotics Prison in Jayapura, focusing on their preparation for social reintegration as responsible and independent individuals. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation, and analyzed with the support of NVivo software to identify key themes. The findings reveal that rehabilitation programs for PNG inmates have not been implemented optimally. Most available programs are limited to personality development activities such as religious guidance, sports, and health services, while access to vocational training remains very limited. Several obstacles were identified, including language and cultural differences, limited facilities, differences in legal systems, and security concerns related to previous escape cases. In addition, the lack of support from the Papua New Guinea Consulate poses a significant barrier to fulfilling the integrative rights of foreign inmates. The study concludes that more adaptive and inclusive rehabilitation programs are needed, particularly those that consider cultural and linguistic differences. Strengthening coordination with the consulate and improving institutional support are also essential to ensure more effective rehabilitation and successful reintegration of foreign inmates into society. Keywords: Rehabilitation; Foreign Inmates; Papua New Guinea; Rehabilitation Barrier;Social Reintegration